Contextual Teaching and Learning Method to Third Year Students of MTsN Balang-Balang Kabupaten Gowa - Nurbaety Halik (Universitas Islam Negeri Alauddin Makassar, 2016)
The objectives of this research were to find out (1) whether or not contextual teaching and learning method improve the reading achievement of the third year students of MTsN Balang-Balang (2) whether or not the students are motivated in learning English reading using contextual teaching and learning method.This research applied quasi experimental design. The subject of the research was the third year students of MTsN Balang-Balang Kabupaten Gowa. The data collected were the students’ reading achievement through test and the students’ motivation of experimental group through quetionnaires. The data from the test and the questionnaire were analyzed quantitatively. The result of the data analysis showed that the mean score of the experimental group was higher than the control group in reading achievement.it is 68.92. The mean score of motivation of the experimental group was 79.9. It means that the students were motivated of Contextual Teaching and learning method. Based on the findings, the writer concluded that the use of Contextual Teaching and Learning Method was effective to increase the reading achivement of the third year students of MTsN Balang-Balang.